Genetics of dieldrin resistance in Culex tritaeniorhynchus - A Prelimenary Report - Mian, Afsar (1979)
Dieldrin resistance allele (D1) was isolated from two wild type stocks of Culextritaeniorhynchus and homozygous colonies laboratory-bred. Larval mortality tests with different concentrations of dieldrin reveal that 0.125 PPM is the best discriminating dose in which all the +/+ larvae die in the first two hours, the D1/+ die between 244 to 8'hours, while D1/D1 remain alive 24 hours after. The data obtained from different genetic crosses indicate that D1 is an incompletely dominant allele, located on the submetacentric chromosome (linkage group II) at a distance of 26.46 plus and minus 1.26 map units from red-potted eye, another autosomal codominant allele